Quick changeover concepts applied : dramatically reduce set-up time and increase production flexibility with SMED - Herr, Karsten (Productivity Press, an imprint of Taylor and Francis, 2013)
Shifting from external to internal set-up steps and optimizing your set-up procedure is only the first step in achieving world-class performance. What's most important is what comes next, cutting down internal set-up times and achieving changeovers that last only a few minutes.Quick Changeover Concepts Applied: Dramatically Reduce Set-Up Time and Increase Production Flexibility with SMED provides a comprehensive overview of changeovers from a strategic, tactical, and operational perspective. It outlines specific strategies that can help readers shorten internal set-up steps through the physical analysis of machine elements. The method presented is the result of a synthesis of Shigeo Shingo's classic single-minute exchange of die (SMED) methodology with modern engineering techniques. Providing readers with the understanding required to significantly reduce internal set-up times, the book explains why efficient changeovers are critical to production scheduling. It redefines set-up and set-up time and details a step-by-step method for developing quick changeover methods in a manner where changes can be realized with minimal spending. Properly implemented, the quick changeover concepts presented, can help you reduce set-up times by up to 95 percent.The book uses language that is easy to understand to make it accessible to all functions along the value stream-from shop floor operators and industrial engineers to machine designers. It introduces the concept of systems engineering, explains the set-up process and its various elements, and addresses the financial aspects of set-up.Maintaining an analytical focus, the text describes the theoretical details and includes numerous application examples for every step. It also includes an extensive chapter on fasteners and connection material that presents alternative methods to connect elements that can save you valuable time.